Concurrent Central Diabetes Insipidus and Acute Myeloid Leukemia - Stephanie L. Pritzl; Daniel R. Matson; Mark B. Juckett; David J. Ciske (Case Reports in Hematology)
Central diabetes insipidus (CDI) is a rare reported complication of acute myeloid leukemia (AML). The onset of AML-associated CDI often precedes the diagnosis of AML by weeks or months and is considered an adverse prognostic indicator in this setting. The mechanism of AML-associated CDI is not known; however, it is often reported in the setting of cytogenetic events resulting in MDS1 and EVI1 complex locus protein (MECOM) gene overexpression. Here, we describe a case of new onset CDI which preceded a diagnosis of AML by 1 month. We detail the clinical and laboratory evaluation of the patient’s CDI, and we describe the pathological and laboratory workup of their AML, which ultimately yielded a diagnosis of AML with myelodysplasia-related changes. Additional cytogenetic findings included the identification of the t (2;3)(p23;q27), which leads to MECOM gene overexpression and which to our knowledge has not previously been reported in the setting of AML-associated CDI. The patient received induction chemotherapy followed by allogeneic hematopoietic stem cell transplantation but experienced disease relapse and passed away nine months after initial diagnosis. We emphasize that new onset CDI can occur as a rare complication of AML where it portends a poor prognosis and may be related to AML subtypes displaying MECOM gene dysregulation.